The Role of Artificial Intelligence in Enhancing Cultural Sustainability Through Visual Design - Hassan, Mona Abd Elsalam (Universitas Komputer Indonesia, 2025)
In the era of rapid technological advancement, Artificial Intelligence (AI) has emerged as a transformative force across various creative industries, particularly in the domain of visual design. This research explores the critical role of AI in promoting cultural sustainability through adaptive and intelligent visual design systems. Cultural sustainability demands the preservation, representation, and dynamic reinterpretation of cultural identities within contemporary visual communication. However, the homogenizing effect of globalization and digital media often threatens the authenticity and continuity of localized cultural narratives. AI technologies—such as generative design algorithms, pattern recognition, and machine learning—offer unprecedented opportunities to counter this trend by enabling culturally sensitive visual content that evolves in response to specific sociocultural contexts. This study adopts a multidisciplinary methodological approach, combining theoretical analysis with applied case studies from branding, visual identity, and immersive digital environments. It examines how AI can be programmed to recognize, learn from, and creatively reinterpret traditional cultural symbols, motifs, and aesthetics without diluting their authenticity. Furthermore, the research proposes a conceptual framework for integrating AI in culturally sustainable visual design, structured around three main dimensions: cultural preservation, adaptive innovation, and ethical AI governance. Special attention is given to the risks of cultural misappropriation, over-automation, and loss of narrative depth when AI applications are not guided by culturally aware design strategies. Ultimately, this study contributes to the fields of visual communication, sustainable design, and cultural informatics by offering a strategic pathway for leveraging AI not as a tool of homogenization but as a catalyst for cultural resilience, diversity, and visual innovation. Keywords: Artificial Intelligence, Cultural Sustainability, Visual Communication, Generative Design, Ethical AI, Cultural Identity